Potential prognostic biomarkers in restenosis of peripheral arteries identified through comprehensive ceRNA network analysis - Miao, Yulin; Li, Zongxin; Sun, Qianqian; Zhao, Gang; Shen, Guohang; Zhang, Haobo; Gao, Fengli (Frontiers in Genetics, 2025)
Peripheral artery disease (PAD) is one of the leading causes of amputation and mortality worldwide, with restenosis being a common complication following vascular interventional therapy that significantly impacts patient prognosis. This study aims to identify potential biomarkers with clinical and prognostic significance for restenosis of peripheral arteries (RPA). To achieve this, RNA expression levels in stenotic vascular tissues from healthy controls and patients with RPA were integrated and analyzed, identifying a growing number of differentially expressed RNAs for the construction of a competitive endogenous RNA (ceRNA) network for prognostic analysis. The analysis revealed that the RNA expression patterns of samples from patients with RPA were significantly different compared with those of healthy controls. Consequently, the resulting differentially expressed RNAs were used to construct a ceRNA network. Through bioinformatics analysis, a complex regulatory network composed of multiple ceRNA axes was established. The findings indicate that key mRNAs in the network play critical roles in various biological functions. Given the prognostic significance of these six differentially expressed genes in RPA, real-time quantitative fluorescence PCR (qRT-PCR) analysis was performed. These results suggest that these candidate key differentially expressed genes are potential prognostic biomarkers for RPA, and their corresponding mRNAs may serve as potential therapeutic targets.